Identifikasi dan Eliminasi Pemborosan Aktivitas pada Proses Produksi Suku Cadang dengan Pendekatan Lean Manufacturing - Agustian Suseno; Hengky Hengky (JIEMS (Journal of Industrial Engineering and Management Systems), 2019)
PT. Trijaya Teknik Karawang is a manufacturing company that produces spare parts, namely the piece pivot. The increased demand make the company parties need to analyze the ability to do the production to make it more effective and efficient in order to win the competition. Preliminary observations on the production floor they still present problems that are categorized as waste. Based on it, lean manufacturing Approach used to solve these problems. First of all the waste identified by mapping the flow of production using Value Stream Mapping (VSM). Then determined the dominant waste going through weighting waste using Waste Assesment Model (WAM) with the result that the inventory is the dominant waste. Next choose a detail mapping tools with Value Stream Analyze Tools (VALSAT) and determine the cause of waste inventory with fishbone diagrams that result, the causes of waste inventory is the breakdown of the machine, the operator of conduct material handling and less nimble, the distance between the machine and the system far, the production batch manufacture. Recommendations for improvements are the application of the system production of one-piece flow with investing buying transfer dies and adds to the human resources division maintenance. The identification of the problem causing factors of the dominant waste activity, namely waste inventory using Fishbone diagrams is lack of engine maintenance because it does not have a maintenance division and the production system used is batch manufacture that produces goods in lot size so that there are WIP parts in each production process.